Arranjo institucional e o padrão de receitas dos municípios sergipanos: um estudo de caso de municípios selecionados nos anos de 2008 a 2012 - Gonçalves, Andersonn Souza (2014)
After the big crisis of 2008, the Federal Government sought to mitigate its effects that could be catastrophic in the Brazilian economy. In order to protect the industry, one of the main actions implemented was to reduce the tax on industrialized products. While actions to protect employment in industries resulted effects, the municipalities have suffered with the decline of the Municipalities Participation Fund (MPF), whose composition is via the collection of the industrial production tax and Income Tax. For municipalities, the reduction of federal transfers showed problems in the process of tax collection of the taxes within their competence. The interest of investigating the institutional scope of the municipal administration appear with this issue, in order to discover the role of institutional design in the performance of their revenues. In the first chapter were treated the elements that form the basis of institutionalist thought, emerging School Institutionalist Original and New Institutional Economics. The following section shows the evolution of the Brazilian tax system in the context of Brazilian municipalities. The paper goes on an analysis of situational variables and variables that are involved in municipal tax profile. It competed the next chapter descriptive analysis and correlation of the qualitative variables, their specificities and their relationship with some situational variables. It was observed that the municipalities that put forward highest contribution of the industry in the composition of their Gross domestic product (GDP) performed better in all of their revenues. Moreover, it emerged the concept that is crucial to the presence and interaction of a number of other institutions, including productive in the local context, bringing a situation to diversify its economy.